Penguatan Program Reseller Guna Meningkatkan Penjualan Pada Usaha Rumahan Produk Olahan Ikan Bandeng - Indah Sulistyowati, Rini; Souisa, Johanis; Januarta, Ganda (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
In Indonesia, small businesses from year to year are increasingly diverse in product goods including clothing, handicrafts, regional specialty products, the most significant of which are food and beverage products. Food and beverages are processed from various basic ingredients, one of which is fish.One of the home business actors in Semarang engaged in the field of milkfish processing. The owner is Mrs. Kurniawati who has a milkfish processing business and already has several resellers but has not optimally or maximally provided a sustainable sales contribution.The current service will involve counseling related to strengthening resellers so that it is hoped that it can increase sales routinely and reach more areas.